Efforts To Improve The Front Rolling Skills Of Class XI.A-1 Students Using Game Methods at SMA N 15 Semarang - Negoro, Muhammad Farkhan Tri; Iswinardi, Iswinardi; Setyawati, Heny (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
The purpose of this research is to find out whether the application of the playing method can improve the learning outcomes of forward guling. The benefit of this research is to provide educators with an overview of the use of appropriate playing methods in teaching and learning activities, so as to improve the quality of learning outcomes. The type of research used in this research is action research and carried out in two cycles, each cycle begins with planning, action, observation, and reflection. The subjects of this study were 36 students of SMA N 15 Semarang grade XI.A-1. Data was collected from observations and results of forward guling learning tests. The results of this study indicate that there is an increase in student learning outcomes, as evidenced in the first cycle of students who succeeded 22 students (61.1%). In cycle II there was a significant increase in that 29 students (80.5%) completed. In addition, the playing method can increase student activity in learning to guling forward. Thus it can be concluded that the application of the effective playing method to improve student learning outcomes in forward guling learning at SMA N 15 Semarang class XI.A-1. To teachers to be able to apply the results of this research on an ongoing basis so that they can apply this playing method as an alternative in the learning process as an effort to improve student learning outcomes, especially gulinging forward.